혈액 투석 환자에서 발생한 자발성 간피막하 혈종 1예 - 형복진; Bok Jin Hyoung; 김은숙; Eun Sook Kim; 이희연; Hee Yeon Lee; 유지한; Ji Han Yu; 윤혜은; Hye Eun Yoon; 양철우; Chul Woo Yang; et al. (Kidney research and clinical practice, 2007)
Spontaneous bleeding in various parts of the body has been reported in patients receiving maintenance hemodialysis, but reports on spontaneous subcapsular hematoma of the liver are scarce. We present a case of spontaneous subcapsular hematoma of the liver which developed in a 53-year-old man with maintenance hemodialysis. He was admitted to our hospital with epigastric pain and abnormal liver function test. On abdominal computed tomographic (CT) scan, a large, well-defined subcapsular mass of the liver with a density consistent with blood was observed. We performed embolization of the bleeding vessel and percutaneous drainage of the hematoma. Five months later, follow up abdominal CT scan revealed a moderate reduction of the subcapsular hematoma. In conclusion, the possibility of spontaneous hematoma of the liver should be considered in hemodialysis patients with epigastric pain, unexplained anemia and abnormal liver function.